Use of residual sludge as a fertilizer on eucaliptus-research diagnosis - Zabotto, Alessandro Reinaldo; Zuñiga, Enrique Alonso; Machuca, Luz María Ruiz; Broetto, Fernando; Tavares, Armando Reis; Kanashiro, Shoey (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2019)
The residual sludge is a contaminating waste, coming from the urban waste treatment process. Its final disposal can become a problem when it is discarded incorrectly, generating serious environmental and health problems. However, it has a high content of organic matter, macro and micronutrients, and can be used in forest plantations as a fertilizer supplement or soil conditioner, being an interesting alternative to its final destination and recycling. Forestry is characterized by providing raw materials for the development of various products based on planted forests. In this context, the eucalyptus crop stands out due to the great importance for Brazilian economy, with an expressive increase in its plantation area in the last decades. Therefore, due to the environmental problems that can be caused by the deposit of residual sludge in the environment, this work aims to diagnose the state of the art of the use of residual sludge in the eucalyptus crop.
Uso de lodos residuales como fertilizante en eucalipto-diagnóstico de investigación
Keywords: Eucalyptus; Forestry; Plant nutrition